2016
DOI: 10.2147/oams.s95159
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of severity of childhood anemia in Malawi: a Bayesian ordered categories model

Abstract: Purpose: This study proposes an ordered categories model, using multinomial cumulative logistic regression, to investigate the risk factors affecting the severity of childhood anemia in Malawi. Patients and methods:We generated a four-category outcome based on the categorization of child hemoglobin (Hb) level: nonanemia (Hb $11 g/dL), mild anemia (10.0 g/dL # Hb # 10.9 g/dL), moderate anemia (7.0 g/dL # Hb # 9.9 g/dL), and severe anemia (Hb ,7.0 g/dL), using the 2010 Malawi Demographic and Health Survey data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
(32 reference statements)
5
15
0
Order By: Relevance
“…The set of explanatory variables used in this study was also used in various studies modeling childhood anemia; [10,11,12,13,15,16,17,18,19] just to name few. Consequently, this forms the theoretical framework that will underpin the current research.…”
Section: Methodsmentioning
confidence: 99%
“…The set of explanatory variables used in this study was also used in various studies modeling childhood anemia; [10,11,12,13,15,16,17,18,19] just to name few. Consequently, this forms the theoretical framework that will underpin the current research.…”
Section: Methodsmentioning
confidence: 99%
“…For example, studies show that the child anaemia prevalence depends on region (e.g. see [47]), therefore we have considered a model that include cross-level interaction, i.e. region by anaemia category interaction to see their joint effect.…”
Section: Multilevel Modelmentioning
confidence: 99%
“…Thereof, this study will be adding to the cur-rent studies that the government and policy makers of these countries are using to allocate resources. A study conducted by [22] in Malawi excluded child nutritional status as covariate, this covariate have been identify by literatures as a significant factor associated to under five mortality. In addition, [25] conducted a study that focused more on child's food consumption variables in Senegal.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…A study conducted by [22] showed that the Malawian policy makers and government need to address poverty, maternal anemia and malnutrition challenges in attempt to reduce the risk of exposing children to anemia condition. In addition, the research by [23] revealed that improving malaria and anemia control in pregnancy will reduce child's risk of suffering from anemic condition.…”
Section: Introductionmentioning
confidence: 99%